REVALUATION OF TANGIBLE ASSETS FROM ACCOUNTING AND FISCAL PERSPECTIVES - MARIANA GURAU; MARIA GRIGORE (Challenges of the Knowledge Society)
Acknowledged by the accounting regulations conform to the European directives inside the alternative assessment norms, the revaluation of tangible assets is also accepted by the International Accounting Standards as an allowed alternative treatment. As there is a real interaction between accountancy and taxation, the present study aims to analyze the fiscal vision on the revaluation, the manner in which the above mentioned accepts the revaluation of tangible assets. It is a known fact that the accounting information is used by the taxation as an object and a support in order to determine and to settle the assessments, the taxes and the contributions. Still, the taxation authority reserves the rights to punctually impose some financial treatments distinct to the accounting rules. This also happens with the revaluation of tangible assets, and this is exactly what we emphasize in the present paper.